Upper Extremity Problems and Functioning in Patients with end Stage Renal Failure Receiving Haemodialysis - Aslı Gençay Can; Canan Çelik; Mustafa Özer; Serdar Kahvecioğlu (Türk Osteoporoz Dergisi, 2017)
Objective: This study aims to evaluate upper extremity problems, upper extremity and hand functions in haemodialysis patients with chronic renal failure and to investigate differences between diabetic and non-diabetic patients. Materials and Methods: Demographic characteristics, upper extremity symptoms, The Quick Disabilities of the Arm, Shoulder and Hand Survey-Turkish scores (Q-DASH-T), Duruoz Hand Index scores, upper extremity locomotor system and neurologic system examinations of 150 haemodialysis patients were evaluated. Results: The most frequently detected problems in upper extremities were shoulder periarthritis (18%) and rotator cuff problems (12%) in all haemodialysis patients. Clinical shoulder periarthritis was detected in 25.4% of diabetic patients and 13.2% of non-diabetic patients whereas there was no statistically significant difference between the groups. Clinical rotator cuff problems were detected in 13.5% of diabetic patients and 10.9% of non-diabetic patients since there was no statistically significant difference between the groups. Carpal tunnel syndrome was detected significantly higher in diabetics compared to non-diabetics (23.7% and 2.2%, respectively). Shoulder circumference, elbow extension, first finger abduction and opposition muscle function weaknesses were significantly more frequent in the diabetic group. In all haemodialysis patients, impaired Q-DASH-T score and Duruoz Hand Index were detected as 30.7% and 16.7% respectively. There were no significant differences in terms of upper extremity and hand functions between diabetic haemodialysis patients compared to non-diabetics. Conclusion: The most common upper extremity problems were shoulder periarthritis and rotator cuff problems in all haemodialysis patients regardless from the presence of diabetes. Carpal tunnel syndrome was found to be more prevalent in diabetic haemodialysis patients compared to non-diabetics. Regardless from the presence of diabetes, impaired upper extremity and hand functions were detected in 30.7% and 16.7% of all haemodialysis patients, respectively.